Enhanced stress prediction correlation for abdominal aortic aneurysm using fluid structure interaction technique - S. K. Elghariani, Badreddin Giuma (2013)
The rupture of the abdominal aortic aneurysm (AAA) occurs when the acting stress exceeds the ultimate stress of the wall. Therefore, the ability to accurately estimate the acting stress is very useful to predict the rupture of an AAA. In this study, previously developed equation which included the effect of inter lumen thrombus, systolic pressure, maximum aneurysm diameter, wall thickness, asymmetry parameter, is improved by applying fully coupling-fluid structure interaction technique (f-FSI). Further improvements of the equation is also done by including the aneurysm length and iliac bifurcation angle. Various case studies are analyzed to investigate the hemodynamic behavior as well as stress distribution on the wall using modified models as well as Computed Tomography scan (CT scan). The results show that the geometry parameters as well as hypertension affect the flow pattern, displacement and stress distribution. Exponential correlation is observed between the maximum acting stress and the asymmetric parameter. In addition, a linear correlation with the maximum aneurysm, aneurysm length, iliac bifurcation angle and wall thickness is determined. The parametric correlations confirm that these geometry parameters are important parameters to predict the maximum acting stress. The inclusion of the effect of hemodynamic by using f-FSI technique predicted a higher maximum acting stress in AAA wall compared to previous equations. Consequently, the current research has concluded that the newly developed equation can be easily used for rupture prediction with even more accurate results than the currently used clinical tools